PENGARUH PENDAPATAN ASLI DAERAH, BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DAN DANA PERIMBANGAN SEBAGAI PEMODERASI DI KABUPATEN/KOTA SUMATERA UTARA - Putra, Ardhansyah (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
The objective of the research was to examine and  to prove empirically the influence of regionally generated revenue and capital expenditures on economic growth in districts/towns of North Sumatera and to examine  balance  fund  as  moderating  variable,  The  population  was  33  districts/towns  (25  districts  and  7 towns) in North Sumatera. The samples (25 districts and 7 towns) had met the criteria during within years of observation so that there were 150 observations. The data consisted of PDRTB (Gross Regional Domestic Product) on constant price in order to find  out the economic growth in districts/towns of North Sumatera, realization  of  PAD  (regionally  generated  revenue),  capital expenditure,  and  balance  fund.  The  data  were obtained  from  the  Central  Bureau  of  Statistics  of  North  Sumatera  and  analyzed  by  using  multiple  linear regression analysis and residual analysis. The result of the research, using t-test, showed that partially PAD had  positive  and  significant  influence  on  economic  growth,  and  capital  expenditure  had  positive  and significant  influence  of  economic  growth.  The  result  of  the  research,  using  F-test,  showed  that simultaneously PAD and capital expenditure had influence on economic growth, while based on residual test it showed that balance fund did not moderate the correlation of PAD and capital expen diture and economic growth..Keywords: Regionally Generated Revenue, Capital Expenditures, Balance Fund, Economic Growth